2020
DOI: 10.1002/1878-0261.12822
|View full text |Cite
|
Sign up to set email alerts
|

EBP2, a novel NPM‐ALK‐interacting protein in the nucleolus, contributes to the proliferation of ALCL cells by regulating tumor suppressor p53

Abstract: The oncogenic fusion protein nucleophosmin-anaplastic lymphoma kinase (NPM-ALK), found in anaplastic large cell lymphoma (ALCL), localizes to the cytosol, nucleoplasm, and nucleolus. However, the relationship between its localization and transforming activity remain unclear. We herein demonstrated that NPM-ALK localized to the nucleolus by binding to nucleophosmin 1 (NPM1), a nucleolar protein that exhibits shuttling activity between the nucleolus and cytoplasm, in a manner that was dependent on its kinase act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
(75 reference statements)
0
3
0
Order By: Relevance
“…Mutant forms of Npm1 were previously associated with different types of leukemias and solid cancers originating from a variety of tissues (Subong et al., 1999; Grisendi et al., 2005; Falini et al., 2005; Uchihara et al., 2021; Kelemen, 2022), and causative effects of mutant forms of Npm1 in hematological cancers initially drew our attention to this factor as one of the outstanding candidates in our interactors list. In a previous study initiated with an unbiased proteomics analysis of Npm1 interacting factors, Gu et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutant forms of Npm1 were previously associated with different types of leukemias and solid cancers originating from a variety of tissues (Subong et al., 1999; Grisendi et al., 2005; Falini et al., 2005; Uchihara et al., 2021; Kelemen, 2022), and causative effects of mutant forms of Npm1 in hematological cancers initially drew our attention to this factor as one of the outstanding candidates in our interactors list. In a previous study initiated with an unbiased proteomics analysis of Npm1 interacting factors, Gu et al.…”
Section: Discussionmentioning
confidence: 99%
“…The nucleolus is a distinct subnuclear compartment, and other than the synthesis and assembly of ribosomal subunits (Pena et al., 2017; Correll et al., 2019; Klinge and Woolford, 2019), it also comprises proteins associated with DNA damage repair, cellular stress response, and factors linking related molecular pathways to the regulation of cell cycle control (Boulon et al., 2010; Yang et al., 2016; Frottin et al., 2019; Correll et al., 2019; Lafontaine et al., 2021). Mutant forms as well as over‐expression of Npm1 were previously associated with different types of leukemias and solid cancers originating from a variety of tissues (Subong et al., 1999; Grisendi et al., 2005; Falini et al., 2005; La Manna et al., 2021a; 2021b; Uchihara et al., 2021; Kelemen, 2022). In light of our recent studies aiming at elucidating the role of Ccdc124 in oncogenic contexts (Arslan et al., 2021), Npm1 has emerged as a paramount candidate warranting further investigation in the current study.…”
Section: Introductionmentioning
confidence: 98%
“…Disruption of the p53-MDM2 interaction by nutlin-3a (a small molecule targeting MDM2) activates the p53 pathway resulting in cell-cycle arrest and apoptosis in ALK+ ALCL cells [ 40 ]. A recent study revealed a novel repressive mechanism of p53 activity by EBP2 in NPM-ALK-expressing cells [ 41 ].…”
Section: Discussionmentioning
confidence: 99%